MODERASI BERAGAMA: PELUANG DAN TANTANGAN DI ERA DIGITAL - M. Amirul Mukhlasin Al Hariri; Mahir Arriyadli Ma'ruf; Saihul Atho’ Alaul Huda (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
Even though the diversity of tribes, ethnicities, races, languages, religions and cultures in Indonesia represent universal laws that emphasize the need for acceptance, they can cause conflict without being accompanied by harmony of understanding. Indonesia is facing the digital era with major problems such as the spread of fake news and the emergence of radicalism and extremism on social media, while facing these complications. This research aims to look at the concept of religious moderation as a solution for managing religious anomalies and distortions in the digital era. Researchers also look at the phenomenon of religious moderation in the digital world. This research finds that the availability of large sources of information, such as narratives, moderate preaching content and videos, provides opportunities for religious moderation. These bases can be well used to spread the values ​​of moderation. Creating digital content to encourage moderation to internet users is an opportunity and a space. On the other hand, radical communities, the spread of fake news, and the polarization of social media, which can enable the development of extreme ideologies, are challenges and problems.